Measuring tenure security of the rural poor using pro-poor land tools: A case study of Itaji-Ekiti, Ekiti State Nigeria - Babalola, Kehinde Hassan (School of Architecture, Planning and Geomatics, 2019)
The sustainable development goals aim to improve the lives of rural dwellers by ensuring the security of tenure of the rural poor. This led researchers and nongovernmental organisations to investigate the security of tenure of the urban and rural poor in developing countries. To improve the security of tenure of the rural poor, many developing countries have initiated programmes that encompass reform of land tenure and land administration systems. To provide a solution to the insecurity of tenure, researchers and non-governmental organisations developed pro-poor land tools to address the gap created by the formal land administration system. To test the developed land tools, researchers apply them in selected case study areas. This study investigates and analyses the tenure security of the rural poor of Itaji-Ekiti, Ekiti State, Nigeria. The New Continuum of Land Rights Model (NCLRM) and the Social Tenure Domain Model (STDM) were applied to land rights types found in the case study. Techniques, theories and tools used were based on a single case study methodology. The mixed methods approach was used to analyse and evaluate the tenure situation in Itaji-Ekiti. This yielded an in-depth understanding of the case. The research further examines critical areas of the Land Use Act of 1978 using the conceptual framework for understanding cadastral system development in customary land rights context. The mixed methodology approach was used in analysing the vital areas of the Act. Land professionals, civil servants and students were the target group that contributed to the study. The research findings showed that security of tenure is weak because every land rights types found in Itaji-Ekiti can be affected by conflicts with customary and informal tenure. The results of this research showed that the Land Use Act is effective in some areas and dysfunctional in others. This is attributed to the age of the Act and many sections of the Act that are not pro-poor. The implementation of the Act showed that it is effective in urban areas while it is not solving land-related problems in rural areas. The research further revealed that the use of case study methodology using mixed methods are suitable for measuring tenure security of the rural poor. The findings provide an understanding of the current land policy in Nigeria and as well as understanding land tenure insecurity in Itaji-Ekiti. The research also provides information for researchers in the field of cadastral system research on the use of propoor land tools as alternative approaches to recording land rights and measuring tenure security of the rural poor.